Assessment of women's needs, wishes and preferences regarding interprofessional guidance on nutrition in pregnancy - a qualitative study - Merle Ebinghaus; Caroline Johanna Agricola; Janne Schmittinger; Nataliya Makarova; Birgit-Christiane Zyriax (BMC, 2024)
Abstract Background A healthy nutrition in pregnancy supports maternal health and fetal development, decreasing the risk for adverse pregnancy outcomes. Guidance by prenatal care professionals can increase women's awareness regarding the importance of nutrition in pregnancy and thereby contribute to a reduced risk for adverse pregnancy outcomes. The aim of this study was to assess the needs, wishes and preferences of pregnant women regarding the interprofessional guidance on nutrition in pregnancy. Methods Using a qualitative approach and a purposive maximum variation sampling strategy, 25 pregnant women were recruited to participate in six semi-structured, guideline-oriented online focus groups. In addition, two semi-structured, guideline-oriented interviews, with a midwife and an obstetrician, were conducted. The focus groups and interviews were audio-recorded and transcribed. Transcripts were analysed using a systematic deductive-inductive approach to qualitative content analysis according to Kuckartz. Results Focus group participants covered diverse perspectives in terms of their age, different models of prenatal care as well as dietary forms from omnivorous to vegan. The majority of women perceived the guidance on nutrition during pregnancy as insufficient. Involved healthcare professionals, namely midwives and obstetricians, should provide more consistent information, especially to avoid uncertainties exacerbated by the internet and social media. There is a need for individual nutrition information regarding dietary supplements and the specifics of different dietary forms during pregnancy, such as a vegan diet. The majority of participants supported the integration of a free-of-charge professional nutrition counselling in prenatal care. Interviews with experts identified time pressure and the complexity of nutrition as a topic as the main obstacles in consultation settings. Both midwife and obstetrician emphasised the need for improved professional education on nutrition in pregnancy in their respective studies. Conclusion Professional guidance for pregnant women on nutrition and uncertainties going along with certain forms of diet during pregnancy could alleviate the burden and overwhelming amount of web-based information. Additionally, information adapted to the needs, wishes and preferences of pregnant women would improve prenatal care through a more personalised approach. The quality of nutrition guidance in pregnancy should be improved by the implementation of this topic in the education of involved healthcare professionals.